Documenting Trauma in Comics
XXI, 345 p. 51 illus., 23 illus. in color.
Keywords: “Documenting Trauma in Comics: Traumatic Pasts, Embodied Histories, and Graphic Reportage brings together a diverse group of scholars to offer a new perspective on representations of trauma in graphic narratives. Using primary source comics from a broad geographic and historical scope, this collection focuses on creating relationships between texts, demonstrating not only the global interest in trauma narratives but also the myriad representational techniques that comics can employ. As such, the coordinates by which this work is steered are academically rigorous, contemporary, and highly topical.” --Professor Harriet EH Earle, Sheffield Hallam University “A necessary collection, both for its crucial global scope and for its contribution to how we think about trauma and images.” --Professor Hillary Chute, Northeastern University Why are so many contemporary comics and graphic narratives written as memoirs or documentaries of traumatic events? Is there a specific relationship between the comics form and the documentation and reportage of trauma? How do the interpretive demands made on comics readers shape their relationships with traumatic events? And how does comics’ documentation of traumatic pasts operate across national borders and in different cultural, political, and politicised contexts? The sixteen chapters and three comics included in Documenting Trauma in Comics set out to answer exactly these questions. Drawing on a range of historically and geographically expansive examples, the contributors bring their different perspectives to bear on the tangled and often fraught intersections between trauma studies, comics studies, and theories of documentary practices and processes. The result is a collection that shows how comics is not simply related to trauma, but a generative force that has become central to its remembrance, documentation, and study. Dominic Davies is a Lecturer in the Department of English at City, University of London. Candida Rifkind is a Professor in the Department of English, University of Winnipeg, Canada.